On the Adaptability and Effect of High Damping Rubber Bearings in the Seismic Resistance of Large Aqueducts - Duoxin Zhang; Yang Yu; Kai Sun; Yanke Shi (Advances in Materials Science and Engineering)
Being the critical hydraulic structure in the construction of national water diversion projects, the large-scale aqueduct is one of the indispensable buildings in the rational allocation of water resources. Moreover, its safe operation during an earthquake is related to the success of the national water network’s construction. In this paper, HDRBs (high damping rubber bearings) have been used as the seismic isolation device for the large aqueduct, considering the FSI (fluid solid interaction) between the water and the walls of the aqueduct, and the mechanical model of HDRBs has been constructed by the bilinear model. The dynamic responses of the large aqueduct under different ground motion excitations, including different peak ground accelerations (PGAs) and operating conditions, have been calculated using the precise integration method. At the same time, the influence of RB (rubber bearings) and HDRBs, two kinds of bearings, on the seismic response of the large aqueduct is compared and analyzed. The maximum reduction in natural frequency with HRDB is about 72%, compared with the use of RB under different working conditions. When there is substitution of HDRB for RB, the stresses in the concrete at the corresponding positions decrease from 1.87 MPa to about 0.71 MPa. The analysis shows that HDRBs are equipped with well seismic isolation and energy dissipation performance, which can effectively reduce the seismic responses and improve the seismic performance of the large aqueduct. In addition, it shows that HDRBs have well adaptability to different operating conditions, ground motion excitation, and PGA, which can be extended to the constructions of aqueduct projects with high seismic intensity and complex geological conditions.